Studi evaluasi penerapan Community Based Tourism (CBT) sebagai pendukung agrowisata berkelanjutan - Sri Endah Nurhidayati (Masyarakat, Kebudayaan dan Politik, 2015)
The role of government in the development of Community Based Tourism (CBT) is very important to strengthen communities around the tourism destination. Government has significant role to ensure that the community has accesses, opportunities and an important power in the development of tourism. The objectives of this research are: (1) describe the government's perception of the  Community Based Tourism (CBT) development, (2) identifying government policies to support the Community Based Tourism (CBT) implementation in Batu City, East Java, and (3) describe the constraints that occur in the implementation of Community based Tourism (CBT) in Batu City, East Java. This study uses qualitative approach by analyzing critical reality, being constructed locally and specifically. The study was conducted in Batu City, East Java. Perceptions of government on the implementation of community-based tourism reflected the mindset of the individual. The community-based tourism development in Batu city is considered the same as rural tourism development. The Government supervise the development of tourism products, especially the tourist village. To support the existence of a tourist village Department of Tourism and Creative Economy   help develop and market promotion. Barriers to the implementation of community-based tourism development with regard to the internal aspects of the government: the quality of human resources decision makers in the Batu Government do not possess educational background of tourism, government people less creative design programs and somewhat forced, the lack of trust the government to local communities, government is not able to map the condition social community related to the system's internal decision-making in the community that are less able to intervene in all components of society, a narrow understanding of CBT, and yet solid government policy coordination between stakeholders. While the external barriers are lack of insight into the capabilities and limitations of the community in terms of tourism, community participation uneven, limited area of Batu, less technological mastery, and the effects of global warming are affecting the climate and cause decreased production and quality apples.